2020
DOI: 10.3389/fpls.2020.563240
|View full text |Cite
|
Sign up to set email alerts
|

Different Age-Induced Changes in Rhizosphere Microbial Composition and Function of Panax ginseng in Transplantation Mode

Abstract: Transplantation is a cultivation mode widely applied in perennial plant growing. This method might be an effective way to alleviate problems associated with continuous cultivation (4–6 years) in ginseng production, but the alleviating mechanism and effects on soil microbial community is unclear. To study this issue, non-transplanted 2-year-old, and 5-year-old (transplantation mode: 2 + 3) and 9-year-old (transplantation mode: 3 + 3 + 3) ginseng rhizosphere soils were analyzed via MiSeq s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 75 publications
1
12
1
Order By: Relevance
“…Soil nutrients are considered an important factor in improving the stress resistance and yield of American ginseng [ 39 ]. Additionally, the transplantation mode directly affects the changes of soil nutrients during its growth [ 40 ]. Similarly, in the present study, the VY4 and CRY4 groups (4 th year of American ginseng cultivation soil) were rich in AN, OP, and AK ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil nutrients are considered an important factor in improving the stress resistance and yield of American ginseng [ 39 ]. Additionally, the transplantation mode directly affects the changes of soil nutrients during its growth [ 40 ]. Similarly, in the present study, the VY4 and CRY4 groups (4 th year of American ginseng cultivation soil) were rich in AN, OP, and AK ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that two spatial variables (PCNM 1 and 3), two climatic variables (MAT and MAP), and three edaphic variables (pH, AN, and AP) were significant in driving bacterial community turnover ( Figure 3B ). Besides the geographic location, plant age could influence the assembly of rhizosphere microbiota ( Micallef et al, 2009 ; Marques et al, 2014 ; Huang et al, 2020 ; Wang et al, 2020 ). Plants can select different microbes at the different stages of development, presumably for specific benefits ( Chaparro et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated root rot in P. notoginseng using the amplicon technologies, such as 16S/18S rRNA sequencing and ITS, and mostly focused on fungi. Even though other species such as Panax ginseng and Panax quinquefolius have been studied ( Xing et al, 2010 ; Vendan et al, 2012 ; Ji et al, 2018 ; Deng et al, 2020 ; Wang Q. et al, 2020 ), reports on the endophytes and rhizosphere microorganisms of P. notoginseng remain limited and no studies have investigated the microbial community of root rot P. notoginseng using metagenomics.…”
Section: Introductionmentioning
confidence: 99%